Characterization of monoclonal antibodies against feline infectious peritonitis virus type II and antigenic relationship between feline, porcine, and canine coronaviruses - Hohdatsu, T. (Arch Virol, 1991)
Seven monoclonal antibodies (MAbs) with neutralizing activity against feline infectious peritonitis virus (FIPV) strain 79-1149 (type II) were prepared. When the polypeptide specificity recognized by these monoclonal antibodies (MAbs) was investigated by Western immunoblotting, all of the MAbs reacted with peplomer glycoprotein (S) of the virus. By competitive binding assay these MAbs were found to recognize at least 3 different epitopes. The reactivity of these MAbs with 6 viruses classified as FIPV type I (UCD-1, UCD-2, UCD-3, UCD-4, NW-1, and Black), feline enteric coronavirus (FECV) type II strain 79-1683, canine coronavirus (CCV) strain 1-71, and transmissible gastroenteritis virus (TGEV) strains TO-163 and SH was examined by neutralization tests. All MAbs neutralized FECV strain 79-1683, CCV strain 1-71, and TGEV strains TO-163 and SH, while they did not neutralize the 6 FIPV type I viruses. Moreover, the MAb against TGEV strain TO-163, which has strong neutralizing activity against 7 TGEV viruses, neutralized CCV strain 1-71, FECV strain 79-1683, and FIPV strain 79-1146, but did not neutralize the 6 FIPV type I viruses. These results demonstrated that there are at least 3 epitopes involved in the neutralization of FIPV type II strain 79-1146, and that these epitopes are not present in FIPV type I viruses but are present in FECV strain 79-1683 which does not induce feline infectious peritonitis, TGEV strains TO-163 and SH, and CCV strain 1-71. These results suggest the presence of 2 serotypes of FIPV which can be clearly distinguished by the neutralization test using MAbs.